Combustion processes inside a direct-fired continuous strip annealing furnace. Issue 20 (2016) - Strommer, Stephan; Niederer, Martin; Steinboeck, Andreas; Kugi, Andreas
Abstract: The combustion process inside a direct-fired continuous strip annealing furnace for steel is analyzed. Here, the fuel-rich combustion of natural gas is modeled by two chemical reactions: first, the oxidation and, second, the water-gas-shift reaction, which leads to a chemical equilibrium inside the furnace. Based on the combustion process, the flue gas dynamics are modeled by the mass and the enthalpy balance. A measurement campaign conducted at a real plant is used for verification of the mathematical model. This model is appropriate for real-time applications in control and optimization due to its low computational effort and high accuracy.